Peru : Revamps its Public Investment System - Frank, Jonas; Guerra-Garcia, Gustavo (World Bank, Washington, DC, 2014)
This chapter assesses the advances and challenges of public investment management (PIM) in Peru. A National Public Investment System was created parallel to other administrative systems and Budgeting reforms. While the country endeavors to improve efficiency in infrastructure spending, several simultaneous reforms have challenged the system and its operation. An ensuing decentralization process, which since 2002 has shifted responsibilities for execution of public investment to subnational governments, created the need for coordination. A new framework for public; private investments meant a new set of rules and regulations was needed. These changes occurred in a period of high and sustained economic growth which provides substantially more resources to executing agencies, thereby challenging execution capacity at all levels of government. At the same time, transfers from natural resources have created spending inequities in a considerable share of subnational governments. These factors together represent a significant challenge in light of uneven institutional capacities across many steps of the investment cycle. In the country s quest to improve public investments pending and outcomes on the ground, it seems worthwhile to proceed in a strategic fashion. In light of the emerging global experience, and given Peru s advances, it seems suitable to focus attention on the following areas: strengthen basic capacities, particularly in human resources; emphasize a strengthening of the implementation stage, particularly with regard to procurement reforms; strengthen coordination across levels of government by mobilizing national and subnational resources towards shared goals; further align processes in Results- based Budgeting (Presupuestopor Resultados) and multi-year programming; and strengthen the demand side from end-users of services.